GREENING THE PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN THE CONTEXT OF IMPLEMENTING A SUSTAINABLE DEVELOPMENT STRATEGY (Innovative professional education, 2024)
The greening of the professional training of future specialists is conditioned by the need of society to implement the vectors of the sustainable development strategy; achieving their understanding of the essence of environmental problems based on the systematic, conscious and complete assimilation of the acquired knowledge; focusing the educational process on the acquisition of experience in environmental protection by future specialists; and the necessary factor – the formation of the readiness of a future specialist to take care of natural resources in the course of their work.
Keywords: environment, sustainable development, greening of education, future specialists, environment, professional training, environmental protection